Review, typology and evaluation of traceability technologies: case of the French forest supply chain. Issue 1 (2nd January 2016) - Saikouk, Tarik; Spalanzani, Alain
ABSTRACT: The use of supply chain management and traceability systems are increasingly important in the forest industry. The adoption of traceability technologies and labelling procedures has become key element to promote the principles of sustainable development in the French forest. This later suffers from a misuse of resources, which negatively impacts the forest ecosystem including the economic competitiveness and biodiversity. However, opting for a suitable technology that resists to the forest environment and does not require a major organisational change is a major challenge for the entire forest supply chain's partners. For this reason, throughout this paper, we suggest a multi-criterion assessment grid to better choose an effective and efficient traceability system, which might include one or more technologies. Thus, our main objective is to review, typologise and evaluate six technologies that could be used in the forest supply chain.